GR24, a synthetic analog of Strigolactones, alleviates inflammation and promotes Nrf2 cytoprotective response: In vitro and in silico evidences. (October 2018) - Tumer, Tugba Boyunegmez; Yılmaz, Berkay; Ozleyen, Adem; Kurt, Begum; Tok, Tugba Taskın; Taskin, Kemal Melik; Kulabas, Seda Savranoglu
Graphical abstract: Highlights: GR24 induced the expression of detoxifying enzymes via Nrf2 activation. GR24 interfered with Keap-1 and Nrf2 binding (in silico). GR24 decreased production/expression of inflammatory mediators in macrophages. GR24 promoted AKT activation in insulin resistant skeletal muscle cells. GR24 downregulated the expression of PEPCK and G6Pase in hepatic cells. Abstract: Naturally occurring phytohormones have shown distinguished potential in chemoprevention and treatment of chronic inflammatory diseases in mammalian cells. Strigolactones (SLs) are a class of carotenoid-derived lactones regulating many aspects of plant development and recently recognized as phytohormones with promising anticancer activity. In this study, GR24, a synthetic analog and representative of SLs, induced the expression of phase II detoxifying enzymes such as HO-1 and NQO1 in hepatic and macrophage cell lines under normal and inflammatory conditions, respectively. This effect has been found to be mediated by Nrf2 activation. In silico molecular docking against 16-mer peptide binding site on Keap1 suggested that GR24 may exert its biological activity by interfering with Keap1 and Nrf2 binding. GR24 also displayed remarkably potent inhibitory activity against the production of nitric oxide (NO) and molecular docking analysis on iNOS supported experimental data. Furthermore, GR24 dose dependently suppressed the LPS–induced iNOS expression at both mRNA and protein level. It also significantly decreased IL-1β release, mRNA expression of IL-1β and COX-2, as well as nuclear accumulation of NFҡB at the low micro molar range in LPS-stimulated murine macrophages. GR24 promoted AKT activation in insulin resistant skeletal muscle cells and downregulated the expression of enzymes, PEPCK and G6Pase control the rate limiting steps of gluconeogenesis in hepatic cells. The results of molecular docking and ADMET analyses indicated that GR24 might be classified as druggable molecule in drug design. Taken together, all results suggest that SLs can be promising multi-potent botanical leads for the mitigation of inflammatory-mediated chronic disorders.